Development of Voice Command Control for Vehicle Mobility - Azahar, Muhamad Amirul; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2023)
A voice command control robot vehicle that can transmit and receive signals when the users give a command to the system, which will navigate the robot to go, back, left, and right. The motivation for this project is due to the remotely controlled system that comes with a variety of inconveniences such as the remote signal being distracted, batteries as the power sources, and infrared cannot penetrate the obstacle. Therefore, the voice command control system was built to improve and resolve the flaws, especially to ease the users with a hands-free experience. An Arduino board is the main component for the prototype which acts as a processor that ensures the data reached the destination while the Bluetooth module serves as an interface to connect the robot vehicle with an android application in a smartphone. From the result analysis, the navigation of the robot vehicle changes based on the specific command given by the user that matched the command that was set in the system. The result of the functionality also was tested based on the distance of the smartphone with the robot vehicle which is limited to 50 meters for the user to pair it. Overall, the voice command control for this robot vehicle can function well.